Strategi peningkatan kapasitas usaha pada pelaku ekonomi melalui digital marketing - Mahadipta, Ngurah Gede Dwi; Pratama, Gede Yudha Anugerah; Prasiani, Ni Komang (Nur Science Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are one of the country's key drivers in promoting economic growth. Digital technology development and changes in consumer behaviour require MSME entrepreneurs to enhance their business capacity, particularly in mastering digital marketing. The main objective of this research is to develop strategies for enhancing business capacity among economic players through digital marketing, specifically for MSMEs in the Province of Bali. The method used in this study is descriptive qualitative with a literature review approach. The results indicate that MSME actors in the Province of Bali need to implement strategic steps to face business competition, including gaining more accessible access to capital and financial literacy with the support of relevant stakeholders, producing potential products, determining product branding and pricing, fostering continuous innovation, and enhancing digital marketing skills through content creation, building engagement to foster loyalty, and applying human-centric principles.